Transcriptomics in advancing portunid aquaculture: A systematic review - Khor Waiho; Mhd Ikhwanuddin; Nor Afiqah-Aleng; Alexander Chong Shu-Chien; Youji Wang; Hongyu Ma; Hanafiah Fazhan (John wiley & Sons Australia, Ltd., 2025)
The rapid advancement of next-generation sequencing technologies has promoted the use of transcriptomics in non-model organisms, including species in the aquaculture sector. Compared to that of other crustacean species, portunid crab aquaculture is impeded by the insufficient knowledge of their biological and physiological processes. This systematic review summarised the advances in transcriptomics in cultured portunid crabs using a systematic literature review methodology. The filtered transcriptome dataset comprised 66 articles from four genera: Scylla, Portunus, Callinectes and Charybdis. At the species level, Scylla paramamosain and Portunus trituberculatus were the two most studied species, highlighting their importance in the aquaculture sector. The affordable cost of RNA sequencing (RNA-Seq) led to an increase in transcriptome-related research in portunid crabs and made available a huge repertoire of differentially expressed genes (DEGs) and single nucleotide polymorphisms (SNPs). We further discussed the transcriptomic advances based on six main functional categories, that is, ‘growth and moulting’, ‘gonadal development and reproduction’, ‘nutrition metabolism’, ‘disease and immunity’, ‘toxicology and stress’ and ‘general transcriptomic profiling’. In general, transcriptomic studies of portunid crabs, specifically the DEGs and pathways allow an in-depth understanding of the biological and physiological processes involved at different growth stages or under various conditions based on the difference in gene transcriptional activity. SNPs obtained from the transcriptome data are useful in many genetic improvementrelated downstream applications, including the construction of genetic linkage maps and as population genetic markers. Future directions, such as hybrid approaches of long-read and common RNA-Seq, and the incorporation of other omics were also discussed.